Strategi Influencer Marketing HAUS! Indonesia Pada Produk Silky Pudding Dalam Membangun Customer Engagement - Nadia Davina Destitha K; Dedi Rumawan Erlandia; Yuliani Dewi Risanti Sunarya (Journal of Creative Student Research, 2024)
Rapid technological developments have made conventional marketing communications turn digital by utilizing the internet and social media. This is felt and done HAUS! Indonesia to create effective, creative and innovative marketing communications strategies. HAUS! Indonesia implements influencer marketing to achieve marketing campaign objectives, one of which is building customer engagement with silky pudding products. The researcher aims to find out and explain the influencer marketing strategy of HAUS! Indonesia on silky pudding products in building customer engagement. This research uses descriptive qualitative methods and collects data through in-depth interviews with 3 informants who are directly involved in influencer marketing activities at HAUS! Indonesia. The results obtained are HAUS! Indonesia divides the influencer marketing strategy into three stages, namely: 1) Planning, determining goals, segmentation, target market, differentiation and product positioning, planning content and message strategy, selecting media, selecting influencers according to criteria, and determining the schedule for uploading influencer content; 2) Implementation, providing direction in the form of briefs, product delivery, checking, approving, uploading content, and interacting with the audience; 3) Evaluation; carried out on insights, sales figures, ratecards, content, communication with influencers, consumer engagement, challenges and obstacles